Gain and bandwidth of InP nanowire array photodetectors with embedded photogated InAsP quantum discs - Jeddi, Hossein; Karimi, Mohammad; Witzigmann, Bernd; Zeng, Xulu; Hrachowina, Lukas; Borgstrom, Magnus T.; Pettersson, Hakan (Nanoscale, 2021)
Here we report on the experimental results and advanced self-consistent real device simulations revealing a fundamental insight into the non-linear optical response of n+-i-n+ InP nanowire array photoconductors to selective 980 nm excitation of 20 axially embedded InAsP quantum discs in each nanowire. The optical characteristics are interpreted in terms of a photogating mechanism that results from an electrostatic feedback from trapped charge on the electronic band structure of the nanowires, similar to the gate action in a field-effect transistor. From detailed analyses of the complex charge carrier dynamics in dark and under illumination was concluded that electrons are trapped in two acceptor states, located at 140 and 190 meV below the conduction band edge, at the interface between the nanowires and a radial insulating SiOx cap layer. The non-linear optical response was investigated at length by photocurrent measurements recorded over a wide power range. From these measurements were extracted responsivities of 250 A W-1 (gain 320)@20 nW and 0.20 A W-1 (gain 0.2)@20 mW with a detector bias of 3.5 V, in excellent agreement with the proposed two-trap model. Finally, a small signal optical AC analysis was made both experimentally and theoretically to investigate the influence of the interface traps on the detector bandwidth. While the traps limit the cut-off frequency to around 10 kHz, the maximum operating frequency of the detectors stretches into the MHz region.
CRIS-Team Scopus Importer:2021-06-11